2013
DOI: 10.1063/1.4798336
|View full text |Cite
|
Sign up to set email alerts
|

High pressure synchrotron x-ray diffraction and Raman scattering studies of ammonium azide

Abstract: Pressure-driven variations of hydrogen bonding energy in ammonium azide (NH4N3): IR absorption and Raman scattering studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 32 publications
6
43
0
Order By: Relevance
“…1 It also exhibits extensive hydrogen bonding between ammonium cation and terminal nitrogen atoms of azide anions. 2,3 Unlike the alkali, alkaline-earth and transition metal azides which are either ionic or covalent, 4 AA is found to have mixed bonding with unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 It also exhibits extensive hydrogen bonding between ammonium cation and terminal nitrogen atoms of azide anions. 2,3 Unlike the alkali, alkaline-earth and transition metal azides which are either ionic or covalent, 4 AA is found to have mixed bonding with unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these studies reveal that vdW-TS method is good enough to reproduce the structural properties of HZA and AA which are closely comparable with the experimental data. 16,20 Therefore, in the present study, we have also used the vdW-TS method to obtain the ground state structures by optimizing the lattice geometry and fractional co-ordinates HZA, respectively, when compared with the experimental results. Here "-" and "+" represent the under-and over-estimation of the calculated results when compared to experimental data.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In addition, understanding the high pressure behavior of HNS become an emerging field of research. 10 16 A series of experimental 15,16 and theoretical 10 14,17,18 studies were reported to explore the electronic structure, mechanical, hydrogen bonding and possible structural phase transitions in HNS under hydrostatic compression. Ammonium Azide (AA) with nitrogen content of 93.3% by weight is proposed to form a polymeric nitrogen (which is a green high energy density material known till date) under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Furthermore, coordination complexes contains ligand and various supramolecular interactions, such as hydrogen bonds, CH … π or π … π stacking, Van der Waals contacts or a combination of these, that intensively affect the properties of substance under high pressure. [8][9][10][11] Previous high pressure studies on the coordination complexes have found various phenomena, including piezochromism, isomerizations, and spin crossover effect. [12][13][14] However, few high pressure studies of energetic coordination complexes have been reported, and high pressure studies of energetic coordination complexes have other problems that we need to solve as follows: (1) the behavior of energetic ligands under pressure; (2) the relationship between flexible structures and pressure.…”
Section: Introductionmentioning
confidence: 99%